2009
DOI: 10.1111/j.1582-4934.2009.00669.x
|View full text |Cite
|
Sign up to set email alerts
|

Akt mediates 17β‐estradiol and/or estrogen receptor‐α inhibition of LPS‐induced tumor necresis factor‐α expression and myocardial cell apoptosis by suppressing the JNK1/2‐NFκB pathway

Abstract: Evidence shows that women have lower tumour necrosis factor-α (TNF-α) levels and lower incidences of heart dysfunction and sepsis-related morbidity and mortality. To identify the cardioprotective effects and precise cellular/molecular mechanisms behind estrogen and estrogen receptors (ERs), we investigated the effects of 17β-estradiol (E2) and estrogen receptor α (ERα) on LPS-induced apoptosis by analyzing the activation of survival and death signalling pathways in doxycycline (Dox)-inducible Tet-On/ERα H9c2 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
66
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 94 publications
(68 citation statements)
references
References 37 publications
0
66
2
Order By: Relevance
“…We found no evidence of a differential activation of inflammatory transcription factors and although estradiol has been shown to inhibit the NFκB response in cardiac myocytes in vitro LPS [39], this would not explain the lack of NFκB activation in the NP mice. However, as our earliest time point was 6 h after LPS, any transcription factor may have been missed.…”
Section: Discussioncontrasting
confidence: 72%
“…We found no evidence of a differential activation of inflammatory transcription factors and although estradiol has been shown to inhibit the NFκB response in cardiac myocytes in vitro LPS [39], this would not explain the lack of NFκB activation in the NP mice. However, as our earliest time point was 6 h after LPS, any transcription factor may have been missed.…”
Section: Discussioncontrasting
confidence: 72%
“…We have previously demonstrated that 17β-estradiol and/or ERα exert cardioprotective effects by suppressing JNK1/2-NFκB-mediated LPS-induced TNFα expression and cardiomyocyte apoptosis via Akt activation [16]. Further unpublished studies in our lab also indicate that E2 and/or ERα could act against protein phosphatase 2A (PP2A)-induced cardiac hypertrophy and BNIP3-induced cardiac autophagy and apoptosis.…”
Section: Introductionmentioning
confidence: 67%
“…More studies have identified that ERα specifically mediate the E2 induced activation of PI3K/Akt signaling pathway in vascular endothelial cells [22][23][24]. Our laboratory previously emphasized that E2 and ERα induce specific Akt and ERK1/2 phosphorylation [16]. In the present study, we focused on the question whether ERβ is also involved in the PI3K/Akt survival pathway.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Vascularsmooth muscle and endothelial cells have been reported to express ERα and Erβ protein & mRNA [34][35][36]. Oestrogen has been proved to have anti-inflammatory effect by acting against inflammatory promoters, such as bacterial cell wall component, lipopolysaccharide (LPS) via activating ERα [37][38][39][40][41][42].…”
Section: Anal Fistula Development and Gendermentioning
confidence: 99%